The response to inactivated influenza A (H3N2) vaccines: the development and effect of antibodies to the surface antigens. - Smith, A. F. (Cambridge University Press, 1977)
A controlled trial of influenza vaccines in a boys' public school from November 1970 to October 1975 provided an opportunity to study the response to vaccine and the effect on subsequent natural challenge in boys with differing natural experience of influenza A strains. The response to influenza A (H3N2) vaccines was assessed by estimating homotypic and heterotypic antibodies to the surface antigens. Previous natural experience of influenza A was found to influence vaccine response and the effect of natural challenge. The antibody response to revaccination with the same strain showed a progressively poorer response to second and third doses. The protectitive effect of naturally acquired and vaccine-induced antibodies was assessed during two outbreaks of influenza A which occurred in the trial period.